The feasibility study of investment in public hospital construction project using the real options model - Hasan Hematyar; Ali Akbari Sari; Davoud Danesh Jafari; Abolghasem Pourreza (Journal of Education and Health Promotion, 2019)
BACKGROUND: The investment decision can be affected by changing levels of uncertainty and risk. The main objective of this research was to identify, characterize, and quantify the parameters which are essential in evaluation hospital construction projects and provide useful modeling techniques to give the best investment decisions for investors in Iran's health-care projects investment. MATERIALS AND METHODS: The methodology of this study was employing discounted cash flow (DCF) and real option valuation to investigate the feasibility investment in the public hospital construction project. The Islamshahr, Mashhad, and Fardis hospitals were included in the analysis. Economic indices of DCF methods were internal rate of return (IRR) and net present value. RESULTS: The economic evaluation of the Black–Scholes model was almost as same as the binomial tree model, but there was a significant difference between the real options model and traditional methods. According to the traditional methods, the profitability with IRR for Islamshahr, Mashhad, and Fardis hospital projects was 35%, 43%, and 26%, respectively. Black–Scholes model showed profitability only for Islamshahr and Mashhad hospitals, and there was no adequate profitability for investors of Fardis Hospital project during the study. CONCLUSIONS: The methods derived from the real options valuation could provide a more flexible and reliable indices for investors in dynamic and high revolution economic conditions. On the other hand, dynamic economic evaluation models can be applied to correctly evaluate the projects because of Iran's health revolution and its health plans.